Isolation and Potency of Symbiotic Nitrogen Fixation Bacteria from Nodules of Falcataria moluccana (Miq.) Barneby & J.W.Grimes for Supporting Nickle Postmining Area Reclamation - Ramdana Sari; Retno Prayudyaningsih (Foresty Faculty of Hasanuddin University, 2020)
Nickel mine is one of the contributors foreign to exchange earners in Indonesia. However, the former mining area creates a complex problem in the physical, chemical, and biological soil properties which directly affect the ability of plant growth for restoration. The planting of legume species, one of them is sengon laut (Falcataria moluccana), in the reclamation of ex-mining land aims to improve soil properties. Legume plants have low C/N ratio so the introduction of nitrogen-fixing soil microorganisms is one alternative that can be used to improvesoil fertility. Nitrogen fixing bacteria can provide nitrogen compounds that can be directly utilized by plants. In addition, the utilization of fast-growing species such as sengon laut is suitable for rehabilitation of critical lands. This study aims to isolate and characterize symbiotic nitrogen fixation bacteria so it can be made as inoculum and applied on revegetation in nickel postmining area. Five bacterial isolates were obtained from nodules of sengon laut belonging to genus Rhizobium(3 isolates) and Bradyrhizobium(2 isolates). All isolates obtained were rod-shaped, Gram negative and did not have endospores. Physiological tests showed that all isolates were aerobic, motile, grew optimally on YEMA media at pH 6 and 7, but did not grow at pH 4. Initial potential testof Acetylen Reduction Assay and IAA test showed that A3.1 SL 5 isolate has the highest value (9.01 ppm and 0.447 ppm) and potential to be inoculum.